Gaya Hidup Hedonisme dan Perilaku Konsumtif Mahasiswa Pengguna E-Commerce - Naufal Zaim Baihaqi Sungkar; Devi Puspitasari; Tatik Meiyuntariningsih (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The rapid growth of e-commerce has made shopping activities more convenient for university students, but it may also increase consumptive behavior. One internal factor associated with such behavior is a hedonic lifestyle, which emphasizes the pursuit of pleasure and personal satisfaction. This study aimed to examine the relationship between hedonic lifestyle and consumptive behavior among university students who use e-commerce. This study employed a quantitative approach with a correlational design. The participants consisted of 103 university students who use e-commerce and were selected through purposive sampling. Data were collected using the Hedonic Lifestyle Scale and the Consumptive Behavior Scale and were analyzed using Spearman's Rho correlation. The findings indicated a positive and significant relationship between hedonic lifestyle and consumptive behavior. Students with a higher tendency toward a hedonic lifestyle also tended to demonstrate higher consumptive behavior. The findings suggest that hedonic lifestyle is strongly associated with consumptive behavior among university students who use e-commerce. Therefore, students are encouraged to manage their lifestyles more wisely to avoid excessive consumption.